ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEMERINTAH DAERAH (Study Empiris Pada SKPD Kabupaten Indragiri Hulu) - Melvi Olinda; Vince Ratnawati; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the good government, internal control, organization culture, leadership style, organization commitment on governance performance. The population in this study were employed who worked in the SKPD Kabupaten Indragiri Hulu (30 government agencies). The sampling method used in this study is proportioned stratified random sampling method. The respondent in this study is the employee Eselon III and Eselon IV SKPD,. The sample used in this study were 100 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0. The result of this study indicated that the good governance, internal control, leadership style, organization commitment has significantly effect on local government performence. Whereas the organizational culture does not affect the performance of local governments. The magnitude of the effect (R2) the good governance, internal control, organization culture, leadership style, organization commitment, the performance of local governments was ,53%. While the remaining 47% is influenced by other independent variabel that are not observed in this study.Keywords: good government, internal control, organization culture, leadership style, organization commitment.